(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This research paper investigates the current situation and reasons behind contemporary improvisational music in China. Through examining the developmental history of improvisational music and clarifying its formation mechanism and characteristics, this paper sheds light on the thought process involved in improvisation and proposes ways to better develop contemporary improvisational music. Three modes of contemporary improvisation performance in China are also explored. The findings of this study contribute to a deeper understanding of the nature of improvisational music and provide insights into its development and future prospects.